The Effect of Sustainability Disclosure and Capital Intensity on Agricultural Firms’ Value with IOS Moderation - Rahmad Simanjuntak; Erlina Erlina; Khaira Amalia Fachrudin (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the effect of Sustainability Report disclosure and capital intensity on firm value, with the Investment Opportunity Set as a moderating variable in agriculture companies listed on the Indonesia Stock Exchange. This research is a quantitative, descriptive study, and data collection technique was obtained from annual reports and Sustainability Reports (SR) reports of agricultural companies listed on the Indonesia Stock Exchange for the 2021-2024 period. The population in this study was 25 agriculture companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used was purposive sampling. The analytical techniques used were multiple linear regression and moderated regression analysis. The results show that economic disclosure, environmental disclosure, social disclosure, and capital intensity have a positive effect on firm value. The Investment Opportunity Set does not moderate the effect of capital intensity on firm value. The Investment Opportunity Set does moderate the effect of Sustainability Report disclosure (economic disclosure, environmental disclosure, and social disclosure) on firm value.